Co-movement of stock market indices between Singapore and her trading partners - Tan, Priscilla (2008)
This paper investigates the price linkages between the equity markets of Singapore and that of Indonesia, Philippines, Malaysia, Taiwan, Hong Kong, United States, Japan and Germany using daily Morgan Stanley Capital International (MSCI) stockmarket data covering the period 1997 to 2001. Cointegration test using the Johansen [Journal of Economic Dynamics and Control, 12, 1988] procedure based on Vector Error Correction Model (VECM) is conducted. The short run dynamic interactions of the markets are also examined.